Cardiovascular events and all-cause mortality in surgically or medically treated primary aldosteronism: A Meta-analysis. (March 2021) - Jing, Ying; Liao, Kangla; Li, Ruolin; Yang, Shumin; Song, Ying; He, Wenwen; Wang, Kanran; Yang, Jun; Li, Qifu; Hu, Jinbo
Objectives: To compare the effect of surgical or medical treatment on the risk of cardiovascular diseases (CVD) and all-cause mortality in patients with established primary aldosteronism (PA). Methods: We searched PUBMED, MEDLINE and Cochrane Library for the meta-analysis. We included patients who were diagnosed with PA following guideline-supported protocols and received surgery or mineralocorticoid receptor antagonist (MRA)-based medical treatment, and age-sex matched patients with treated essential hypertension (EH). Primary endpoints were CVD incidence and all-cause mortality. Results: Compared with EH, patients with treated PA had a higher risk of CVD [odds ratio (OR) 1.79; 95% confidence interval (CI) 1.39–2.31]. This elevated risk was only observed in patients with medically treated PA [OR 2.11; 95%CI 1.88–2.38] but not in those with surgically treated PA. The risk of all-cause mortality was significantly lower in patients with treated PA [OR 0.86; 95% CI 0.77–0.95] compared to EH. The reduced risk was only observed in patients with surgically treated PA [OR 0.47; 95% CI 0.34–0.66], but not in those with medically treated PA. Conclusions: Patients with medically treated PA have a higher risk of CVD compared to patients with EH. Surgical treatment of PA reduces the risk of CVD and all-cause mortality in patients with PA.